The ER Stress Inducer l-Azetidine-2-Carboxylic Acid Elevates the Levels of Phospho-eIF2α and of LC3-II in a Ca2+-Dependent Manner - Gemma Roest; Evelien Hesemans; Kirsten Welkenhuyzen; Tomas Luyten; Nikolai Engedal; Geert Bultynck; Jan B. Parys (Cells, 2018)
Accumulation of misfolded proteins in the endoplasmic reticulum (ER) activates the unfolded protein response (UPR) to reduce protein load and restore homeostasis, including via induction of autophagy. We used the proline analogue l-azetidine-2-carboxylic acid (AZC) to induce ER stress, and assessed its effect on autophagy and Ca2+ homeostasis. Treatment with 5 mM AZC did not induce poly adenosine diphosphate ribose polymerase (PARP) cleavage while levels of binding immunoglobulin protein (BiP) and phosphorylated eukaryotic translation initiation factor 2α (eIF2α) increased and those of activating transcription factor 6 (ATF6) decreased, indicating activation of the protein kinase RNA-like ER kinase (PERK) and the ATF6 arms of the UPR but not of apoptosis. AZC treatment in combination with bafilomycin A1 (Baf A1) led to elevated levels of the lipidated form of the autophagy marker microtubule-associated protein light chain 3 (LC3), pointing to activation of autophagy. Using the specific PERK inhibitor AMG PERK 44, we could deduce that activation of the PERK branch is required for the AZC-induced lipidation of LC3. Moreover, both the levels of phospho-eIF2α and of lipidated LC3 were strongly reduced when cells were co-treated with the intracellular Ca2+ chelator 1,2-bis(O-aminophenoxy)ethane-N,N,N′,N′-tetraaceticacid tetra(acetoxy-methyl) ester (BAPTA-AM) but not when co-treated with the Na+/K+ ATPase inhibitor ouabain, suggesting an essential role of Ca2+ in AZC-induced activation of the PERK arm of the UPR and LC3 lipidation. Finally, AZC did not trigger Ca2+ release from the ER though appeared to decrease the cytosolic Ca2+ rise induced by thapsigargin while also decreasing the time constant for Ca2+ clearance. The ER Ca2+ store content and mitochondrial Ca2+ uptake however remained unaffected.